Mediação de conflitos escolares e justiça restaurativa. - Costa, Silvana Ferreira Magalhães (2012)
This research investigated the feasibility and the effectiveness of conflict mediation with restorative justice methods as an alternative means to prevent school violence, according to the perspective adopted by the Program School Protection System, implemented by the State Board of Education in the public school network of São Paulo State. Conflict mediation was implemented in São Paulo State public schools by means of the School Protection System with the purpose to protect state schools against risk factors, vulnerability, and to reduce violence within schools. Such a measure was carried out by means of contracting a School Mediator Teacher, whose main assignment is to adopt restorative practices and to mediate potential conflicts within schools. The aims of the research were: to analyze the Pedagogical Proposal and the By-laws of two public schools within the range of the Education Superintendency of Mirante do Paranapanema-SP; to identify the concept of school violence in the perception of the mediating teacher and to analyze the effects of conflict mediation based on restorative justice methods as an alternative means to prevent school violence. This research was guided by a methodological procedure of qualitative character, whose data collecting devices were documental analysis and semi-structured interviews with mediating teachers. Based on the data collected by us, it was possible to find out the meaningful improvements which conflict mediation had in the management of conflicts within schools. On the other hand, one also managed to find out the subsistence of strong traits displayed by traditional culture, inherently retributive/punitive, to deal with conflicts in everyday life within schools. Mediation ruled by restorative principles shows itself as a possibility meant for contributing on behalf of an education in favor of citizenship awareness, engaged in the development of citizens aware of their rights, capable of assuming their responsibilities within society. Although conflict mediation is a brand new approach in the field of education, one managed to realize that the theoretical foundation met the need of our study, making the discussion and the analysis of purposes easier.